The collective excitations and static dipole polarizability in small nanoparticles - Leiro JA (WILEY, 2022)
Collective dipole excitations for small clusters have been considered in the energy range close to the visible light. The absorption energies and static dipole polarizabilities are estimated. In the case of Ag-8, Na-18, Na-20, Cs-40, Mg-10, Ba-20, Ag-9(+), Na-21(+), and Mg-11(++) clusters, a semiclassical density functional method with the Thomas-Fermi approximation has been used. Also, applications in Al-6, Al-7, (ZnS)(3), and (ZnSe)(4) will be discussed. The results are compared with the available data.